2000
DOI: 10.1034/j.1600-0447.2000.102001032.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging in childhood‐ and adolescence‐onset schizophrenia associated with obsessive‐compulsive symptoms

Abstract: Reduced size of the left hippocampus in the SOCS+ group supports a neurodevelopmental etiology in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Magnetic resonance imaging studies have identified significantly reduced volumes in the left hippocampus, frontal lobes (Aoyama et al 2000) and anterior horn of the lateral and third ventricle (Goldstein et al 1999) for schizophrenia patients with OCS when compared with their schizophrenia counterparts without OCS. Additionally, schizo-obsessive patients show more neurological signs (Sevincok et al 2004), motor symptoms including catatonia, loss of motor ability or hyperactive motor activity (Tibbo et al 2000) and extrapyramidal symptoms (Kruger et al 2000 ;Ohta et al 2003 ;Mukhopadhaya et al 2009) compared with schizophrenia subjects ; and more tics when compared with patients with OCD (Poyurovsky et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging studies have identified significantly reduced volumes in the left hippocampus, frontal lobes (Aoyama et al 2000) and anterior horn of the lateral and third ventricle (Goldstein et al 1999) for schizophrenia patients with OCS when compared with their schizophrenia counterparts without OCS. Additionally, schizo-obsessive patients show more neurological signs (Sevincok et al 2004), motor symptoms including catatonia, loss of motor ability or hyperactive motor activity (Tibbo et al 2000) and extrapyramidal symptoms (Kruger et al 2000 ;Ohta et al 2003 ;Mukhopadhaya et al 2009) compared with schizophrenia subjects ; and more tics when compared with patients with OCD (Poyurovsky et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another MRI study, conducted in 2000 by Aoyama et al [17], found significantly reduced volumes of the left hippocampus, frontal lobes and anterior horn of the lateral and third ventricles in the schizo-obsessive group (n = 15) compared to the SCZ group (n = 17) and healthy controls (HC; n = 19); an inverse correlation between illness duration and frontal lobe size was also found in schizo-obsessive patients but not in SCZ patients. …”
Section: Resultsmentioning
confidence: 99%
“…One [9] of the above-mentioned original research articles was discarded as unrelated to the topic. In addition to our PubMed search, another 4 relevant neuroimaging studies in schizo-obsessive disorder (all original research reports) were also included in this report, based on our knowledge of the subject [16,17,18,19]. All articles were written in the English language.…”
Section: Methodsmentioning
confidence: 99%
“…[5] Obsesif-kompulsif belirtileri olan erken başlangıçlı şizofreni hastalarının manyetik rezonans gö-rüntüleme (MRI) çalışmalarında obsesif-kompulsif belirtileri olmayan şizofre-ni grubuna ve kontrol grubuna göre anlamlı derecede küçük sol hippokampus belirlenmiştir. [40] Bu araştırmacılar obsesif-kompulsif belirtileri olan şizofreni grubunda, obsesif-kompulsif belirtileri olmayan gruptan farklı olarak; hastalık süresi ile frontal lob büyüklüğü arasında ters yönde bir ilişki olduğunu bulmuşlardır. Bu anlamda bu hastaların frontal lob atrofisi açısından yatkınlık geliştirdikleri ileri sürülmektedir.…”
Section: Nöro-görüntüleme çAlışmalarıunclassified